Pernikahan Tidak Tercatat (Sirri) pada Masyarakat Medan Estate Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Manshur uddin (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This scientific article is based on a research entitled “The cause of the legal to the unlisted marriege in the Medan Estate Society Percut Region Sei Tuan Deli Serdang District.” This research is field of research that used case study approach, done in the Medan Estate Society Percut Region Sei Tuan Deli Serdang District. And it can be concluded that the unlisted marriege practice or Sirri mariage in the Medan Estate Society Percut Region Sei Tuan Deli Serdang District is common, it was done in accordance to the islamic marriage, fulfilled the islamic pillars and conditions. The thing that differenciate in the practice is the marriage is not listed by the marriage registrar (VAT) in the Office of Religious Affairs (KUA), only the certicate from the chief of the society and environment as the evidance of legal marriage (marriage contract). The validity of Sirri marriage according to the community is valid in accordance to the law, if the marriage has to meet the conditions stipulated in Islamic law. As for the legal status of marriage Sirri in the perspective of positive law is invalid, and all the implications that arise in them are considered illegal.